IMPLIKASI YURIDIS NIKAH SIRI DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Nunung Nugroho (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2019)
Undang-Undang No. l Tahun 1974 In people's lives there is still a frequent way of marriage which is a violation of Law , especially article 2 paragraph 2, namely: